P-56 An evaluation of the satisfaction level and change in knowledge level towards advance care planning (ACP) among heart failure patients using a pre and post survey. (1st September 2015) - Ng, Clarice SH; Tan, SH; Lim, SM; Lau, Cindy SL; Wong, Jane CQ; Tan, BC; Wong, G; Sim, KLD
Abstract : Background: No previous evaluation was carried out to determine the satisfaction and knowledge of ACP among heart failure patients in Singapore. Aim: Study the impact of ACP on heart failure patients using a pre and post survey in National Heart Centre Singapore (NHCS). Methods: Pre survey with patients who consented to ACP discussion during screening and follow up with post survey via telephone by the ACP clinical coordinators two weeks after the first ACP discussion. Results: Pre-survey (N = 94), 82.4% never heard of ACP, 95.6% had no written documentations on their end-of-life preferences, 60.4% were comfortable to discuss end-of-life preferences, 34.1% had thought about their preferences. Post-survey (N = 88), 82.1% rated satisfied or very satisfied with the ACP discussion. 67.9% felt that it helped them reflect their personal values and identify end-of-life preferences. 71.4% had good understanding towards ACP and 74% had improved health knowledge after the discussion. 93.4% agreed that planning for end-of-life care preferences is important. Discussion: The awareness of ACP is low among NHCS patients. Majority of patients believe that it is important to plan for their healthcare wishes but very few have initiated this conversation or documented their wishes with their healthcare providers or their family members. Conclusion: More publicity is needed to promote the literacy of this ACP Programme among Singaporeans, especially those with unpredictable disease trajectories. Findings show that the Programme is beneficial to patients who are ready for such discussion. A more proactive approach by healthcare stakeholders is needed to expand this Programme.